LEGISLATIVE CHANGES RAGARDING TRAFFICKING AND EXPLOITATION OF VULNERABLE PERSONS – EVOLUTION AND CURRENT JUSTIFICATIONS - Constantin, Eduard (International Journal of Legal and Social Order, 2025)
The intensification of the phenomenon of exploitation of vulnerable people, the serious ways in which this phenomenon manifests itself, and its cross-border character have led the legislator to intervene on the normative content of some crimes regarding the trafficking and exploitation of vulnerable people in the current Criminal Code, by changing the amount of punishments and by introducing new assimilated variants and aggravating elements – the latest amendments were introduced by Law No. 217 of 10 July 2023, Law No. 202 of 26 June 2024, and Law No. 269 of 30 October 2024. The justification for these legislative amendments referred to the high rate of human trafficking, the large number of children abused and sexually exploited by being forced into prostitution or into acts specific to child pornography, in the online environment, but also to the cross-border nature of human trafficking. Other reasons were also presented, such as: the significant proportion of other forms of exploitation (forced labor, begging); very lenient sentences compared to the seriousness of the crimes of trafficking and exploitation of vulnerable persons; the need to restrict the scope of application of the provisions on the suspension of the execution of the sentence under supervision in the case of slavery, human trafficking and minors trafficking; the lack of differences between the social danger of pimping in its aggravated form and human trafficking; non-uniform judicial practice.